Mammalian Retroelements - Deininger, Prescott L.; Batzer, Mark A. (Genome Research, 2002)
The eukaryotic genome has undergone a series of epidemics of amplification of mobile elements that have resulted in most eukaryotic genomes containing much more of this ‘junk’ DNA than actual coding DNA. The majority of these elements utilize an RNA intermediate and are termed retroelements. Most of these retroelements appear to amplify in evolutionary waves that insert in the genome and then gradually diverge. In humans, almost half of the genome is recognizably derived from retroelements, with the two elements that are currently actively amplifying, L1 and Alu, making up about 25% of the genome and contributing extensively to disease. The mechanisms of this amplification process are beginning to be understood, although there are still more questions than answers. Insertion of new retroelements may directly damage the genome, and the presence of multiple copies of these elements throughout the genome has longer-term influences on recombination events in the genome and more subtle influences on gene expression.